The prognostic and predictive value of peripheral immune-related proteins in patients with lung cancer treated with radiotherapy - Lyu, Shaowen; Vaes, Rianne D. W.; Laven, Iris E. W. G.; Cortiula, Francesco; Hendriks, Lizza E. L.; Vooijs, Marc A.; De Ruysscher, Dirk K. M. (Frontiers in Oncology, 2025)
Lung cancer is the leading cause of cancer-related death world-wide. Although the standard of care for patients with advanced stage lung cancer has significantly improved with the advent of immunotherapy and targeted agents, the overall prognosis remains poor. It highlights the need for improved patient selection utilizing prognostic and predictive biomarkers. Given the limited feasibility of serial lung tumor tissue biopsies, liquid biopsies have gained specific interest in achieving this aim. Radiotherapy, commonly used alongside systemic treatments, can induce the release of immuno-stimulatory and immuno-suppressive molecules, triggering the immune- and inflammatory responses and releasing associated molecules. This review specifically focusses on immune-related molecules that are measurable in the blood and which have potential prognostic and/or predictive value in patients with lung cancer treated with radiotherapy alone or in combination with systemic agents. Such immune-related molecules include cytokines and chemokines, damage-associated molecular patterns, soluble receptors and ligands, and proteins expressed on the immune cell surface of circulating immune cells. Classical cytokines IL-6, IL-8, and TGF-β1 were the most studied molecules in patients with lung cancer treated with radiotherapy and were associated with poor survival and increased risk of radiation-induced toxicity. To date, there are still some barriers before these promising findings can be implemented in regular clinical practice. Practical points to achieve this goal are also addressed in this review.